Robotic Surgery for Large Renal Stones: Prospective Three Years Single-Institution Experience - Ahmed J. Al Sayyad, (Journal of King Abdulaziz University: Medical Sciences, 2023)
This prospective study evaluates the role of robotic surgery in the management of large renal stones. Robotic renal stone surgery is safe and effective, and may be considered among the treatment options for large renal calculi in adults, especially for patients with concomitant ureteropelvic junction obstruction. The benefits brought by robotic systems include improved 3-D visualization, greater dexterity, precision, and increased range of motion. Thus, robotic pyelolithotomy has been recommended for the treatment of renal calculi with concurrent upper tract abnormalities. The efficacy and safety of robotic pyelolithotomy as a treatment of large renal pelvic stones and partial staghorn stones is evident in our study, with a substantially high stone clearance rate. We were able to complete the robotic procedures safely and successfully in all but one of our 38 patients, who was converted to open surgery due to bleeding and severe adhesions. Overall, we found this procedure feasible, safe, efficacious, and high yielding in the management of large renal stones, especially when the procedure is accompanied by renal pelvis reconstructive surgery.